P09.18 Suboptimal prenatal testing for syphilis and other stds among commercially-insured women in the united states, 2013. (13th September 2015) - Tao, G; Neblett Fanfair, R; Owusu-Edusei, K; Gift, T; Bernstein, KT
Abstract : Background: Prenatal syphilis screening is a critical step in the prevention of congenital syphilis infection. US guidelines recommend universal syphilis screening of all pregnant women at the first prenatal visit and again early in the third trimester and at delivery for at risk women. Methodology: We analysed a large commercial claims database to estimate prenatal testing coverage for syphilis among pregnant women aged 15–44 in 2012–2013. We used procedural and diagnostic codes to identify pregnant women with a live birth in 2013. Pregnant women were included if they were enrolled in health plans at least 210 days prior to the date of delivery. Procedural codes were used to identify syphilis, HIV, and other STD testing during prenatal period, defined as 40 weeks before and on the date of delivery. Results: Among 346, 811 pregnant women, 82.4% had syphilis testing before the 28th week of pregnancy or before the third trimester, 84.3% before the 37th week of pregnancy, and 85.3% at any point during the prenatal period. Of these 346, 811 women, 71.2% also had testing for HIV, 83.7% hepatitis B, 68.0% chlamydia, and 67.3% gonorrhoea during the prenatal period. Of 61, 112 pregnant women without prenatal syphilis testing before the third trimester, only 16.6% had any syphilis testing in the third trimester or on the date of delivery. Of 285, 699 pregnant women with prenatal syphilis testing before the third trimester, only 22.5% had any syphilis testing in the third trimester or on the date of delivery. Conclusions: Prenatal screening for syphilis, HIV, and other STDs was suboptimal. Low syphilis testing during the third trimester or on the date of delivery among all pregnant women, especially among pregnant women without syphilis testing before the third trimester, leaves a critical gap in the prevention of congenital syphilis infection. Interventions should be developed to increase prenatal syphilis testing as recommended.